2014
DOI: 10.4103/0974-8490.121451
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of the hydroalcoholic extract from Lepidium meyenii (Brassicaceae) and Fagara tessmannii (Rutaceae) on male sexual organs and hormone level in rats

Abstract: Background:Lepidium meyenii is a plant, which has been used in folk medicine to treat infertility and to increase sexual desire. However, few reports have investigated the administration of this plant with other plants having the same properties.Objective:The present investigation was designed to evaluate whether the combination of Lepidium meyenii and Fagara tessmannii can improve spermatogenesis and testosterone level in rats.Materials and Method:Twenty male rats were treated daily for 2 weeks with the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…The higher testosterone level that was associated with the high dose of F. tessmannii was responsible for normalising the sperm transit time (Lembe et al, ). It is believed that the combination of L. meyenii (black maca) with F. tessmannii improves gonadal activities of rats only at higher doses of F. tessmannii irrespective of whether F. tessmannii was administered alone (Lembe et al, ) or in combination with L. meyenii (Lembe et al, ). This information appears to contradict the traditional belief that F. tessmannii is used for infertility treatment (Ayofor et al, ), except if doses of the alcohol extract up to 1 g/kg body wt.…”
Section: Fagara Tessmannii (Zanthoxylum Tessmannii)mentioning
confidence: 88%
See 2 more Smart Citations
“…The higher testosterone level that was associated with the high dose of F. tessmannii was responsible for normalising the sperm transit time (Lembe et al, ). It is believed that the combination of L. meyenii (black maca) with F. tessmannii improves gonadal activities of rats only at higher doses of F. tessmannii irrespective of whether F. tessmannii was administered alone (Lembe et al, ) or in combination with L. meyenii (Lembe et al, ). This information appears to contradict the traditional belief that F. tessmannii is used for infertility treatment (Ayofor et al, ), except if doses of the alcohol extract up to 1 g/kg body wt.…”
Section: Fagara Tessmannii (Zanthoxylum Tessmannii)mentioning
confidence: 88%
“…The authors further observed that low doses of F. tessmannii extract facilitated epididymal sperm transit, a mechanism thought to be responsible for the decrease in sperm quality and DSP of rats, whereas higher doses could normalise the transit sperm time and increase the DSP, sperm count and testosterone concentration (Fernande, Porto, Arena, & Kempinas, ; Lembe, Gasco, & Gonzales, ; Lembe et al, ). Enhanced spermatogenesis was also observed especially at the length of stages VII‐VIII and IX‐XI of the seminiferous tubule, suggesting that F. tessmannii must act at the initial stages of spermatogenesis (Lembe et al, , ). The observed deficit in gonadal weights along with decreased sperm count, DSP and testosterone concentration especially with the lowest dose of F. tessmannii (0.01 g/kg body wt.)…”
Section: Fagara Tessmannii (Zanthoxylum Tessmannii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lembe et al, (2014) evaluaron los efectos de la combinación de Lepidium meyenii y Fagara tessmannii observaron que en dosis altas se observa un aumento significativo (P<0.05) del conteo espermático El efecto observado del H. rosasinensis en la motilidad individual y las subpoblaciones espermáticas podría estar mediado a través de cambios en la concentración de calcio, que es inversamente proporcional al movimiento. Los iones de bicarbonato activan la cAMP, lo que ha llevado a la protein Kinase C a ser uno de los reguladores del movimiento espermático (Mortimer, 1997), y cambios en la composición o el pH del plasma seminal pueden ser la causa de las diferencias en motilidad individual.…”
Section: Los Estudios Existentes De Efectos Del H Rosa-sinensis Son unclassified
“…They concluded that camu camu had potential effects improving spermatogenesis and co-administered with maca increased stages of mitosis, meiosis and spermiation of the spermatogenic cycle of rats. Administration of a hydroalcoholic extract of Fagara tessmannii (1 g) and Lepidium meyenii (black maca) (50 mg) together to rats significantly increased the number of spermatids, epididymis sperm count, daily sperm production and serum testosterone concentration when compared to the control (Lembè et al 2014 ). The results indicated that the combination of Lepidium meyenii (black maca) with Fagara tessmannii could improve male reproductive organs activities in rats.…”
Section: Animal Studiesmentioning
confidence: 99%